Does the 2015 Peace Accord in Mali Reflect the Priorities of Households and Local Leaders? - Lendorfer, Julia; Hoogeveen, Johannes (World Bank, Washington, DC, 2016)
Using unique household level data collected in northern Mali in August and September 2015, this paper explores whether the content of the 2015 Peace Accord reflects the concerns and priorities of the citizens, local leaders, and refugees, or whether it is an exclusive agreement between elites who fail to represent the interests of the population at large. The study finds that local leaders’ opinions are appropriate proxies for the citizens they represent, and most (but not all) of the measures stipulated in the Peace Accord align. The greatest divergence between citizen preferences and actions specified in the Peace Accord is the emphasis in the latter on road infrastructure. When different activities are costed, this disconnect becomes very apparent. The bulk of funds (45 percent) are apportioned to infrastructure construction, while the typical respondent prefers job creation; the poorest prefer investments in social services. However, most of infrastructure spending has been earmarked for the medium term. Short-term priorities reflect the preferences of the population in northern Mali much better. It is concluded that although the Peace Accord had all the elements to be an exclusive elite pact, its priorities largely reflect those of the population, granting it much higher probability of success.